The effect of tetracycline and erythromycin in a model of acne-type inflammation. - Dalziel, K. (1987)
The effects of systemically administered oxytetracycline and erythromycin in a guinea pig model of acne-type inflammation were assessed histologically and by tissue measurement techniques. It was found that oxytetracycline significantly reduced the volume and maximum area of inflammation compared with both control and erythromycin treated groups. Oxytetracycline also altered the morphology of the inflammatory infiltrate significantly reducing the proportion of polymorphonuclear leucocytes present. In this model, erythromycin did not alter the inflammatory response but did seem to reduce the amount of transepidermal elimination of inflammatory debris.